2017
DOI: 10.1111/1467-923x.12405
|View full text |Cite
|
Sign up to set email alerts
|

The 2017 General Election, Brexit and the Return to Two‐Party Politics: An Aggregate‐Level Analysis of the Result

Abstract: The outcome of the 2017 general election—a hung parliament—defied most predictions. In this article, we draw on aggregate‐level data to conduct an initial exploration of the vote. What was the impact of Brexit on the 2017 general election result? What difference did the collapse of UKIP make? And what was the relative importance of factors such as turnout, education, age and ethnic diversity on support for the two main parties? First, we find that turnout was generally higher in more pro‐remain areas, and plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 2 publications
5
39
0
1
Order By: Relevance
“…Heath and Goodwin's () analysis of constituency‐level data show that Conservatives made gains from the electoral decline of UKIP in Leave‐supporting areas, but lost in more Remain‐supporting areas with large number of graduates and younger voters. There was also a slight tendency for Labour to perform better in Remain‐supporting constituencies (Heath and Goodwin, ). Jennings and Stoker, in their study of aggregate‐level constituency data, however, reject the description of the 2017 election as a ‘Brexit election’, since ‘the vote is better seen as a symptom of the longer‐term bifurcation of politics; less revenge of the “Remainers” and more a continuing battle of mobilisation between cosmopolitan and non‐cosmopolitan areas’ (Jennings and Stoker, , p. 359).…”
Section: A Brexit Election?mentioning
confidence: 99%
“…Heath and Goodwin's () analysis of constituency‐level data show that Conservatives made gains from the electoral decline of UKIP in Leave‐supporting areas, but lost in more Remain‐supporting areas with large number of graduates and younger voters. There was also a slight tendency for Labour to perform better in Remain‐supporting constituencies (Heath and Goodwin, ). Jennings and Stoker, in their study of aggregate‐level constituency data, however, reject the description of the 2017 election as a ‘Brexit election’, since ‘the vote is better seen as a symptom of the longer‐term bifurcation of politics; less revenge of the “Remainers” and more a continuing battle of mobilisation between cosmopolitan and non‐cosmopolitan areas’ (Jennings and Stoker, , p. 359).…”
Section: A Brexit Election?mentioning
confidence: 99%
“…The NME exit poll [9], and data from both Ipsos MORI [10] and the Essex Continuous Monitoring survey [11], pointed to there having been a considerable increase in youth turnout in the general election, and that this had contributed to the hung Parliament. Early research by Heath and Goodwin found that the biggest increases in turnout occurred in constituencies with the largest numbers of young people [12]. Organisations such as Bite the Ballot and the National Union of Students (NUS) campaigned to both register young people and persuade them to cast their ballots, and a sizeable number of young people registered to vote in the weeks after the general election was called [13,14].…”
Section: The Emergence Of the Youthquake Narrativementioning
confidence: 99%
“…Entre tanto, el líder de los laboristas aceptó la posición del Brexit. En las nuevas elecciones generales, la tendencia se revirtió: el laborismo se hizo más fuerte, y el UKIP y los conservadores perdieron fuerza (Heath y Goodwin, 2017).…”
Section: Brexitunclassified